EARTHQUAKE BEHAVIOR OF BREAKWATERS SEATED ON LIQUEFIABLE SOILS - Selcuk, Murat E.; Ozaydin, Kutay; Berilgen, Mehmet (YILDIZ TECHNICAL UNIV, 2012)
One of the most important problems seen in soils under the influence earthquake motion is liquefaction phenomena. Liquefaction problems were widely observed in 1999 Kocaeli Earthquake in our country. After this devastating earthquake great loss of life and property and large effects to economy took place. Not only do port structures support country's economy which is surrounded by water on three sides, but also will have a great responsibility in enabling aid to be delivered after the expected Marmara earthquake. For this reason it is very important for the breakwaters to fulfill their duties, which is to protect the port structures, after earthquakes. In this study, behavior of breakwaters built on liquefiable soils under earthquake effects is investigated. 1g scaled model experiments are done on a shaking table built in the laboratory. According to model experiment results, liquefaction is observed in the first cycles of cyclic horizontal displacement motion when the magnitude of input acceleration is sufficiently high. Moreover, failure occurs at the toe of breakwater due to liquefaction.
Keywords: Liquefaction; breakwater; Engineering